Parasitic worms of the central nervous system: an Australian perspective. - Hughes, A.J.; Biggs, B.A. (2002)
The diagnosis and management of parasitic diseases of the central nervous system (CNS) is difficult, even for infectious diseases physicians and neurologists. Furthermore, few overviews of the spectrum of causative helminths and clinical syndromes have been published. In the present study, we review the seven most common parasitic diseases of the CNS: (i) cysticercosis, (ii) neuroschistosomiasis, (iii) paragonimiasis, (iv) angiostrongyliasis, (v) hydatid disease, (vi) sparganosis and (vii) gnathostomiasis. Major syndromes of parasitic disease of the CNS and their differential causes are discussed, including: (i) cystic lesions, (ii) enhancing granulomas (with and without creeping subcutaneous eruptions), (iii) eosinophilic meningoencephalitis and (iv) spinal cord disease. Specific risk factors that predispose to these infections are also discussed and particular attention is drawn to the situation in Australia.